Characteristics and Performance of Family Businesses in Wuse Market, Abuja, FCT Nigeria - Agbim, Kenneth Chukwujioke; Tanko, Ibrahim; Paul, Vincent (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
The unprecedented uncertainties in the Nigerian business environment is negatively impacting business operations and performance. Yet, literature on the association between business characteristics and the financial and non-financial performance of family trading businesses in the Nigerian context is overtly and seemingly scant. Again, family trading businesses are prevalent in Wuse market; one of the largest markets in Abuja, FCT. Taken together, this study seeks to investigate the effects of business characteristics on the financial and non-financial performance of family trading businesses in the market. A cross-sectional survey research design, and criterion and systematic sampling techniques were adopted to collect data from 211 founder/CEOs and the descendant/CEOs of family trading businesses in the market via questionnaire. The generated data were subjected to linear regression analysis. The results showed positive and significant effects. The study concludes that the computation of the overall performance of the businesses based on financial and non-financial performance measures show higher overall performance than when they are computed using financial performance measures alone. Education of the founder/CEOs and descendant/CEOs on how to keep financial records of business transactions, collect the non-financial data based on the non-financial performance measures, and how to use same for the computation of non-financial performance were recommended. The researcher advocates a replication of the study in other contexts using an expanded scope and qualitative or triangulation method.